Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.17794/rgn.2018.5.5
|View full text |Cite
|
Sign up to set email alerts
|

Ground Temperature Monitoring for a Coaxial Geothermal Heat Exchangers Field: Practical Aspects and Main Issues From the First Year of Measurements

Abstract: Ground temperature at shallow depths (< 50 m) is not stable, nor in space, neither in time, and its behaviour is the result of the superimposition of eff ects of heat pulses of diff erent origin: solar, geothermal and anthropic. The correct assessment of ground temperature is a crucial point when designing a shallow geothermal energy system. In geothermal closed loop projects using short borehole heat exchangers, the ground temperature has more variability and aff ects the rate of heat extraction/injection. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It is worth mentioning that MEMS have a 360° measuring range, while electrolytic cells feature a full-scale value of ±25°. Additionally, the structure of MUMS-based arrays permits the exploitation of different sensor typologies in the same array, such as piezometers to detect water level variations [ 24 ] or high-accuracy thermometers to have a detailed description of the underground temperature at different depths [ 25 ]. Finally, IoNH allows the acquisition and elaboration of monitoring data sampled by traditional instrumentation featuring an analog output signal (e.g., extensometers, crack meters, load cells, etc.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth mentioning that MEMS have a 360° measuring range, while electrolytic cells feature a full-scale value of ±25°. Additionally, the structure of MUMS-based arrays permits the exploitation of different sensor typologies in the same array, such as piezometers to detect water level variations [ 24 ] or high-accuracy thermometers to have a detailed description of the underground temperature at different depths [ 25 ]. Finally, IoNH allows the acquisition and elaboration of monitoring data sampled by traditional instrumentation featuring an analog output signal (e.g., extensometers, crack meters, load cells, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Besides the eight CB-HEs, three Observation Boreholes (OBs) have been installed to monitor the ground temperature. Further details of the geology and hydrogeology of the area, the monitoring strategy and the system layout can be found in Tinti et al [19].…”
Section: Borehole Heat Exchangers' Fieldmentioning
confidence: 99%
“…Finally, it has been used as a benchmark for evaluating the performance of other modelling tools (Nam and Ooka [37]). Specifically to the FEFLOW® model of the CB-HE field installed in the Tribano area, the validation was performed comparing the simulated temperature changes in the ground nodes with the measured values from the monitoring points in the three observation boreholes, which can be found in [19]. The details of the model realized in FEFLOW® can be found in [34].…”
Section: Validation Of the Sequential Coupled Simulatormentioning
confidence: 99%
“…Evaluating spatial soil temperature distribution during the geothermal system operation is of major importance in analysing SGE performance as well as its sustainability, e.g., [18,22]. The authors in their study [23] reported the thermal effect of the Borehole Heat Exchangers (BHE) on the ground temperature by monitoring a borehole located 1 m away from one BHE. This study highlighted the importance of long-term and multiyear monitoring to evaluate the effect of system operation on the entire ground impacted by the presence of BHEs.…”
Section: Introductionmentioning
confidence: 99%